Quantitative musculoskeletal monitoring and analysis in aquatic rehabilitation - Amin, Abu Bony; Asabre, Ebenezer; Razaghi, Sina; Noh, Yeonsik (Frontiers in Electronics, 2025)
The benefits of aquatic rehabilitation have been demonstrated to promote wellbeing and facilitate motor recovery in middle-aged adults and geriatrics. Individualized patient-centered treatment is essential to accelerate and improve the rehabilitation process of neurological and orthopedic patients. Although aquatic therapy and rehabilitation are well known to be beneficial to these populations, it can be challenging for therapists to visualize and monitor patient progress and provide individualized feedback to ensure correct movement as planned. To establish the suitability of the developed wearable device in an aquatic environment, this study compared the extracted features of the sEMG and IMU data in on-land and aquatic environments for the bicep curls (BC) and tricep kickback (TK) protocols. We conducted a systematic analysis of the reproducibility and precision of the sEMG-IMU characteristics to assess the feasibility of the device for practical applications. While time and frequency domain features of sEMG were higher in aquatic environments compared to on-land, the Intraclass Correlation Coefficient (ICC) for these features ranged from 0.81 to 0.98, and the Coefficient of Variation (CV%) exhibited a range of 5.7% to 14.4%, highlighting reproducibility and correlation across environments in the two protocols. Environment. Moreover, for frequency domain the reproducibility and precision of the sEMG recordings for each muscle in this study were obtained high (ICC=0.92−0.96, CV%=5.4−13.8%). It’s noticeable that the observed acceleration data is almost similar to the same movement was maintained throughout the exercise. Eventually, the quantitative result is used to cluster the protocol types along with various repetitions to promote the personalized aquatic rehabilitation.